Alternative communication for children with Autism Spectrum Disorder in the global context: Scope review protocol (Research, Society and Development, 2022)
Objective: To map the scientific evidence in the literature on alternative communication in children with Autism Spectrum Disorder. Revision Method: Scoping Revision Protocol following the Joanna Briggs Institute method. For this study, publications that mention or use of alternative communication in children with autism will be included. It will be searched in the data banks of the Biblioteca Virtual em Saúde (VHL), Portal da Capes and PubMed, along with the Chinese literature and representative entities. Presentation and Interpretation of two results: Descriptively, tables and charts will be used to present the revision scores.